2006
DOI: 10.1007/s11248-006-0017-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Newcastle disease virus fusion protein in transgenic maize and immunological studies

Abstract: Transgenic plants have been employed successfully as a low-cost system for the production of therapeutically valuable proteins, including antibodies, antigens and hormones. Here, we report the expression of the fusion (F) gene of the Newcastle disease virus (NDV) in transgenic maize plants. The expression of the transgene, driven by the maize ubiquitin promoter, caused accumulation of the F protein in maize kernels. The presence of the transgene was verified by Southern and western blots. Feeding chickens with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(32 citation statements)
references
References 41 publications
2
28
0
1
Order By: Relevance
“…This study obtained a higher level of expression than ever reported. The level of expression obtained in this study is comparable to results obtained by others in maize when expressing the spike protein of the transmissible gastroenteritis coronavirus and the fusion protein of Newcastle disease virus (Lamphear et al 2002;Guerrero-Andrade et al 2006). In sera, mice were seronegative at the start of the experiment, but by day 90 post-vaccination, titers varied by more than 0.5 IU.…”
Section: Immunogenicity Of Rabies Virus Antigen Expressed In Plantssupporting
confidence: 84%
“…This study obtained a higher level of expression than ever reported. The level of expression obtained in this study is comparable to results obtained by others in maize when expressing the spike protein of the transmissible gastroenteritis coronavirus and the fusion protein of Newcastle disease virus (Lamphear et al 2002;Guerrero-Andrade et al 2006). In sera, mice were seronegative at the start of the experiment, but by day 90 post-vaccination, titers varied by more than 0.5 IU.…”
Section: Immunogenicity Of Rabies Virus Antigen Expressed In Plantssupporting
confidence: 84%
“…Representative plant species expressing the oral vaccine are potato, tomato, and tobacco; additionally, maize, rice, carrot, and soybean are also applied in this field [41,42,43,44,45,46,47,48,49]. Those plants are mainly focused on traditional and usually eaten crops in human, because it is known that inexperienced plants sometimes have problems with certain plant allergies.…”
Section: Plant-based Expression System For Vaccine Developmentmentioning
confidence: 99%
“…These experiments proved that HN and F proteins can be successfully expressed in transgenic plants and that obtained proteins are immunogenic when delivered to either mice or chickens. Both maize-produced NDV F protein (Guerrero-Andrade et al, 2006) and tobacco-produced HN protein (Hahn et al, 2007) have been found to be immunogenic in orally immunized chickens; oral immunization with F protein gave 100 % protection of chickens against nasal challenge with NDV, while in the case of HN protein protection against nasal NDV challenge failed but the authors reported a big increase in anti-HN serum IgG levels 28 days after vaccination, increased by 2-fold in 40 % of examined chickens and 4-fold in 20 % of examined chickens (Hahn et al, 2007). HN and F proteins, co-expressed in potato, have been shown to elicit anti-NDV antibodies in intraperitoneally immunized mice and serum IgG at levels comparable to those elicited in mice fed with nontransformed plants soaked in NDV (Berinstein et al, 2005), while the intestinal fluids of those mice also showed considerable IgA and IgG levels.…”
Section: Newcastle Disease Virusmentioning
confidence: 99%